Income Distribution and Economic Growth: A Critical Approach - Arestis, Philip; Baltar, Carolina Troncoso (Panoeconomicus, 2017)
The aim of this paper is to review the Kaleckian and post-Kaleckian literature on income distribution and economic growth and question the extent to which they analyse countries’ economic regimes and economic performances properly and appropriately to understand countries’ economic performances. The debate focuses on the inclusion of profit margin in the investment function as a way to characterize the effective demand regime in the neoliberal era as a profit-led growth regime. Our argument is that this inclusion is not able to evaluate properly the countries’ economic growth in terms of the consistency between its effective demand regimes and income distribution. Key words: Effective demand regime, Income distribution, Economic growth, Kalecki. JEL: E12, E25, O40. Cilj rada je da se razmotri Kalecki i post-Kalecki literatura o raspodeli dohotka i ekonomskog rasta i prouči u kojoj meri ona pravilno i na odgovarajući način analizira ekonomske režime zemalja i ekonomske performanse kako bi se shvatili ekonomske performanse zemalja. Debata se fokusira na uključivanje profitne margine u funkciju investicije kao način da se okarakteriše režim efektivne tražnje u neoliberalnoj eri kao režimu koji je usmeren ka rastu profita. Naš argument je da ovo uključivanje nije u stanju da pravilno proceni privredni rast zemalja u smislu konzistentnosti između njihovih režima efektivne tražnje i raspodele dohotka. Ključne reči: režim efektivne tražnje, raspodela dohotka, ekonomski rast, Kalecki.